The Impact of Role Models on Sexual Minority Women: A Qualitative Interview Study - Khushi Mann; Salina Tesfamichael; Katharine A. Rimes (Behavioral Sciences)
Sexual minority women (e.g., lesbian, bisexual, pansexual) have increased risk of experiencing various mental health problems compared to sexual minority men and heterosexual individuals. Sexual minority women (SMW) have also been found to have lower self-esteem than heterosexual women, which could contribute to poorer mental health. Previous findings suggest that role models could potentially be used to improve LGBTQ+ wellbeing. The current exploratory study investigated SMW’s experiences about the impact of role models or the lack of them and their views about how role models could be used to increase the self-esteem of SMW in potential interventions. Semi-structured qualitative interviews were conducted with 17 SMW. Using thematic analyses, four themes about characteristics of role models were developed: “Similar to me”, “Self-confident about being different”, “Strong and kind”, and “Source of learning and support”. Three themes about the impact of role models were identified: “Increased self-esteem”, “Inspiring personal growth”, and “Lack of role models: I don’t belong”. Content analyses indicated a wide range of ideas about how role models could be used within individual or group self-esteem interventions. Future research could apply these findings to develop or enhance interventions to increase the self-esteem of SMW.